Changes in Slight and Extreme Precipitation Events From 1963 to 2017 Over Northern Xinjiang, China - Li, Minggang; Zhao, Yong; Li, Yang; Zhou, Xin; Zhang, Shaobo (Frontiers in Earth Science, 2021)
Based on daily measured data from 25 stations in Xinjiang Province from 1963 to 2017, we discuss the statistical characteristics, linear trends, and temporal concentration of slight precipitation (SP) and extreme precipitation (EP) events, and consider relationships between SP and EP events and daily mean temperature. The results show that SP events contribute strongly to the total annual number of wet days, and that EP events contribute strongly to the total annual precipitation amount. In consist with the decrease in SP events and the increase in EP events over the 55-year period, the contribution of SP events to total annual number of wet days has decreased significantly while the contribution of EP events to total annual precipitation amount has increased significantly. SP event usually distributes through most months of the year, whereas EP event usually concentrates in summer (JJA). Influenced by the negative trends for SP events frequency and positive trends of EP events frequency during recent decades, the concentration degree for SP and EP events have significantly increased and decreased, respectively. Distinct differences are found between the relationships of SP events and EP events to daily mean temperature. The daily mean temperature recorded at the stations in Northern Xinjiang on days with SP events was between –35°C and +34°C, and for EP events ranged from –21°C to +30°C. Regionally averaged curves for the change in SP and EP event frequency with temperature have bimodal and unimodal distributions, respectively. Trends for daily mean temperatures and for the frequency of SP events at different temperatures agree well over nearly the entire temperature range, while trends for daily mean temperatures and for the frequency of EP events at different temperatures are not always consistent. These results will help to improve our understanding of the characteristics and variability of precipitation in arid regions within the context of climate warming.